The Role Of Drones In Accelerating The Arrival Of Medical Support Before The Arrival Of Ambulances In The Kingdom Of Saudi Arabia (The Review of Diabetic Studies, 2025)
This study aimed to identify the role of drones in accelerating the delivery of medical support before ambulances arrive in the Kingdom of Saudi Arabia, given the challenges field teams may face, such as traffic congestion or geographical distance from accident sites. The study relied on the descriptive analytical approach due to its suitability to the nature of the research, where the questionnaire was used as the main tool to collect data from a sample of 30 individuals working in the Saudi Red Crescent Authority. The results showed a general trend among sample members toward agreeing that drones contribute to improving the speed of medical response and help deliver essential supplies such as medicines and resuscitation equipment faster than ambulances in some cases. Participants also indicated that the use of drones contributes to improving the chances of saving lives in remote or crowded areas and provides field teams with accurate and immediate information about the accident site, enhancing decision-making efficiency and speeding up intervention. The study recommended expanding the use of drones as part of the Saudi Red Crescent's future development plans, while also providing specialized training programs for paramedics to enhance their proficiency in using this technology. It also recommended conducting broader studies with larger samples to measure the long-term impact of these applications on the quality of emergency medical services.